On Human Rights and the Qurâanic Perspective: Freedom of Religion and the Rule of Apostasy - Almirzanah, SyafaÃ¢Â€Â™atun (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2007)
It is often argued that Islam is not compatible with modernity. This can be seen for instance in the fact of the problem that Islam faces to the challenge of universal values of human rights. Built on this supposition, the present article discusses on the great extent the question of religious freedom in Islam. As freedom of religion in the framework of universal declaration of human rights can mean as freedom to change religion, this contradicts to Islamic prohibition of apostasy, punishable with death penalty. The author argues that Islam in fact guarantees religious freedom. This is clear from the Quranic injunctions assuring the freedom of choice whether to embrace Islam or not. Such a freedom is however often contradicted to one prophetic tradition sanctioning death penalty for apostasy. In her view, the author believes that the hadith more in attunes to the political strategy of the prophet to safe Muslim community from any acts of treason or sedition. Death penalty for apostasy is thus not related to the mere personal crime of changing religion but more that of public law related to war or crimes against state. More relying on the modern interpretation of the Quranic verses as well as the prophetic traditions, the author concludes that Islam is in conjunction with the modern values of religious freedom in which personal choice of religion or belief is the backbone of human rights.